Multistage optimization of a non-institutional investor’s assents portfolio - M. A. Khalikov; D. A. Maksimov (Путеводитель предпринимателя)
The article deals with the statement, mathematical model and features of numerical algorithm of solving the dynamic discrete task for optimization of financial assets portfolio of a non-institutional investor. Structure and element content of the model are substantiated including optimality and limits criteria. It is given a numerical method for search of optimal solution that is based on local optimization of continuous task solving. New criterion of effective management and evaluation method of fair rate of return of operations with assets portfolio within a certain time horizon are offered.